Needs Analysis of Class XII Students of MA Raudlatul Ulum on the Development of a Recitation Program as an Interactive Learning Media on Magnetic Field Material - Isna Fatimatuzzahroh; Parno Parno (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to analyze the needs of Class XII students of MA Raudlatul Ulum for the recitation program as an interactive learning media on magnetic field material. This research’s method is descriptive. The research subjects are class XII students of MA Raudlatul Ulum who have taken magnetic field subject. The data collection techniques are interview with 1 teacher who teaches magnetic field subject and questionnaires for 30 students. Based on the data obtained, we identified several problems that occur in the magnetic field material, including (1) the lack of time allocation in the learning process despite the magnetic field material being a broad and complex material, (2) the lack of feedback in learning, (3) less interactive and boring learning media used, (4) lack of practice questions. Referring to these problems, it is necessary to develop a recitation program as an interactive learning media on magnetic field material. This program contains practice questions accompanied by feedback on each correct or incorrect answer.